The application on the usage of natural fibers as noise absorbers - Madlan, Mohd Amran (2013)
The Heat Ventilation Air Conditioning System (HVAC) is one of the ducting systems that are commonly found to make occupants in the building comfortable by controlling the temperature and air flow. However, noise is produced in the system and reaches the occupants inside the building, thus causing distraction, discomfort and uneasiness. There are HVAC silencers in the market, however the typical sound absorbing material used is mineral wool types. This research focuses on the ducting silencer with the sound absorbing material that made from Coconut fiber, Arenga Pinnata (Ijuk), Kenaf, Cotton and Rockwool. The compositions of these materials have been tested to identify its performance. The objective of this research is to compare the insertion loss in the HVAC by using various configurations. The materials have been tested separately at various frequencies to determine the effects of the forward airflow in the HVAC system in the transmission loss and to analyse the affect of the insertion loss on the straight and bend in the HVAC duct system. The experiment that was carried out follows the standard ASTM E477. In this experiment, the sound absorbing material of Coconut fiber with different configuration has been investigated, followed by other types of sound absorptive materials such as Arenga Pinnata (Ijuk), Kenaf, Cotton and Rockwool. From the overall result and comparison, all the materials that tested on straight and bend ducting showed the same performance trends where at below frequency of 500 Hz the insertion loss was high at certain frequency only. The insertion loss increases steadily from 500 Hz until 6300 Hz and maintained until frequency 10000 Hz at around 6 dB to 40 dB. The insertion loss increase as the numbers of sound absorptive materials in the silencer increase but the 4 pieces configuration has been chosen as the best configuration because the air flow was higher around 60% compared to configuration of 5 pieces. The insertion loss of 30g Rockwool combined with 30g viii Cotton was higher compared to other materials which are averagely 44.8% higher than Rockwool alone, 44.1% higher than Cotton alone, 35% higher than Kenaf alone, 81.4% higher than combination of Arenga Pinnata and Kenaf, 65.1% higher than Coconut fiber alone, and 118.9% higher than Arenga Pinnata alone. The insertion loss at straight and bend ducting that was analysed showed that the bend ducting gave more insertion loss at an average of 47% than the straight ducting.